2016
DOI: 10.19173/irrodl.v17i6.2803
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Members’ Instructional Priorities for Adopting OER

Abstract: This study aimed to investigate and classify faculty members' instructional priorities for adopting OER.In-depth interview data were collected from 10 faculty members from different regions and analyzed with NVivo 10. The original supposition was that the well-established instructional priorities, effectiveness, efficiency, and appeal would apply. However, it was found that in adopting OER, these faculty members had four instructional priorities: effectiveness, efficiency, appeal, and extension.Effectiveness w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
(18 reference statements)
0
2
0
3
Order By: Relevance
“…Guo et al (2015) believed that OER is the bundle of learning resources that can be used and adjusted by the user without any legal and economic restrictions. Jung and Hong (2016) defined OER as study materials with an intellectual property license that permits repetition in use and distribution. Additionally, OER include full courses, programs, syllabi, curricula, teachers' guides course materials, modules, learner guides, teaching notes, textbooks, e-texts, research articles, videos, audio tracks, assessment tools and instruments, interactive materials such as simulations and role plays, experiments, demonstrations, databases, software, apps (including mobile apps), and any other materials that have been designed for use in teaching and learning used to support access to knowledge that is openly available for use by educators and learners, without an accompanying need to pay royalties or license fees (Atkins et al, 2007;Hylén & Schuller, 2007;UNESCO, 2002;UNESCO & Commonwealth of Learning, 2011).…”
Section: What Are Oer and Oep?mentioning
confidence: 99%
“…Guo et al (2015) believed that OER is the bundle of learning resources that can be used and adjusted by the user without any legal and economic restrictions. Jung and Hong (2016) defined OER as study materials with an intellectual property license that permits repetition in use and distribution. Additionally, OER include full courses, programs, syllabi, curricula, teachers' guides course materials, modules, learner guides, teaching notes, textbooks, e-texts, research articles, videos, audio tracks, assessment tools and instruments, interactive materials such as simulations and role plays, experiments, demonstrations, databases, software, apps (including mobile apps), and any other materials that have been designed for use in teaching and learning used to support access to knowledge that is openly available for use by educators and learners, without an accompanying need to pay royalties or license fees (Atkins et al, 2007;Hylén & Schuller, 2007;UNESCO, 2002;UNESCO & Commonwealth of Learning, 2011).…”
Section: What Are Oer and Oep?mentioning
confidence: 99%
“…The topic of OEP and IDs specifically is limited in research and can be extended more broadly to include educators and faculty. In one study, Jung and Hong (2016) examined faculty members' instructional priorities for adopting OER and found that effectiveness, efficiency, appeal and extension were the most important factors. Kaatrakoski, Littlejohn and Hood (2017), in examining the tensions experienced by educators as they adopt OEP, note that "previous studies on the use of OER suggest that while educators are slowly adopting Open Educational Practice, there remains limited understanding of breadth of teaching and learning practice that OER enable."…”
Section: Instructional Designers and Oepmentioning
confidence: 99%
“…Cabe aclarar que cada participante podía seleccionar más de una opción, y que en general, tanto hombres como mujer tienen como primera opción adaptar los recursos de tal forma que se ajuste a sus necesidades particulares. Fuente: elaboración propia, con base en el cuestionario realizado Un aspecto clave al utilizar recursos creados por terceros es la procedencia y la calidad de los mismos [2], [32], [33]. A este respecto se les consultó a los docentes qué importancia le dan a la procedencia y a los creadores de dichos recursos.…”
Section: B Cultura De Usar Y Compartir Recursos Educativosunclassified
“…Fuente: elaboración propia, con base en el cuestionario realizado A los participantes se les consultó, en una pregunta abierta, cuáles eran las principales razones para utilizar materiales de otras personas y sus comentarios enfatizan los siguientes aspectos: la posibilidad de actualización con nuevas tendencias en el área, contar con distintas perspectivas, tener la posibilidad de ofrecerle a los estudiantes material innovador, un considerable ahorro de tiempo y esfuerzo y mejorar la calidad de los recursos utilizados. Estas respuestas son consistentes con los hallazgos de [33], quienes clasificaron los motivos para utilizar recursos en 14 dimensiones.…”
Section: B Cultura De Usar Y Compartir Recursos Educativosunclassified
See 1 more Smart Citation